Physical activity level and mental health effects on academic performance post COVID-19 pandemic among students in UiTM Pahang - Md Hamdan, Nur Fikriyah Izzati; Abdul Razak, Fatin Aqilah; Ahmad, Mohd Faridz; Yulianto, Ari Gana; Shahudin, Nurul Nadiah (Faculty of Sports Science and Recreation, 2025)
The global COVID-19 pandemic caused enormous changes in the educational system, with students shifting to distance learning and experiencing significant changes in their academic norms. Presently, the pandemic’s transition to online learning has raised concerns about students' general state after COVID-19 pandemic, particularly their academic performance and well-being. The overarching purpose of this study is to determine the effects of physical activity and mental health on academic performance among students at the University of Technology Mara, Pahang Branch, Jengka Campus after COVID-19 pandemic. Data were collected from 354 students, including 196 diploma and 158 degree-level students, using questionnaires. The analysis was conducted using Spearman’s rank correlation. This study utilized the Depression, Anxiety, and Stress Scale (DASS21) and the Global Physical Activity Questionnaire (GPAQ) to assess psychological distress and physical activity levels, respectively. The study shows that a significant majority of students engage in moderate physical activity, while sedentary behavior is prevalent. Concerningly, a sizable proportion of students reported signs of mental health problems such as depression, anxiety, and stress. The findings also show that there is no substantial association between physical activity and academic performance. However, the study does find a small but statistically significant inverse relationship between mental health and academic performance, implying that students with higher total mental health scores may have slightly lower CGPAs. As a result, the findings highlight the significance of encouraging physical activity and treating mental health problems among university students, particularly in the post COVID-19 pandemic era. These findings are beneficial for encouraging the development of strategies and support services to focus at enhancing students' overall well-being and academic success.